The Adoption, Acceptance, and Perceived Usefulness of Health Information Systems: A Scopus-Based Bibliometric Review Using VOSviewer (2014-2024) - Alikha Rahma Aurea; Pribadi, Firman (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: The integration of Health Information Systems (HIS) has transformed healthcare by incorporating systems for acquiring, processing, analyzing, and sending critical information, therefore enhancing management efficiency. This study aimed to identify users' adoption, acceptance, and perceived utility of HIS using bibliometric analysis of the Scopus database from 2014 to 2024, concentrating on the literature regarding HIS. Methods: The present research utilized a bibliometric methodology. This study includes 418 articles from the Scopus database that met the inclusion criteria. Inclusion criteria were limited to English-language articles and review papers published between 2014 and 2024. Duplicate records and non-open-access publications were excluded. The dataset was transformed into RIS and CSV formats and analyzed using VOSviewer, applying clustering, overlay, and density visualization techniques to reveal thematic structure, collaboration patterns, and the temporal evolution of research on HIS. Results: The United States leads in HIS publications, contributing 137 articles between 2014 and 2024. The Journal of Medical Internet Research is the most prolific journal with 16 articles, and Bates, D.W., is the leading author with 7 publications. Key factors influencing HIS adoption and acceptance include technological infrastructure, user training, and organizational support. Theories such as the Technology Acceptance Model (TAM) and Unified Theory of Acceptance and Use of Technology (UTAUT) are commonly applied to explain acceptance by users and managers. Keyword analysis revealed major themes including patient care, telemedicine, mHealth, COVID-19 impacts, acceptance, and satisfaction. Perceived benefits driving HIS utilization involve time-saving, effort reduction, cost efficiency, and overall effectiveness. Conclusion: The effective implementation of HIS depends on elevated levels of user acceptance and perceived usefulness, which directly affect the purpose of utilizing these technologies. The utilization of HIS enhances satisfaction among healthcare providers and patients, while also reducing healthcare costs and improving clinical procedures and care quality.